THE PROBLEM OF PROFESSIONAL ORIENTATION OF HIGH SCHOOL STUDENTS (EDUCATION IN THE 21ST CENTURY, 2025)
In modern conditions, the problem of professional orientation of high school students is relevant and is in the focus of attention of researchers. A young person, as a future specialist, tries to find his place among the professions, passing a long path of acquiring knowledge. Meanwhile, the large flow of information often makes it difficult for a high school student to independently orient himself in the matter of choosing a profession. In this matter, both the family (parents) and the school (specialist, social pedagogue) play an important role, whose effective guidance and support will not only help the child in choosing a profession, but will also ensure the economic, social, scientific development of society.
Keywords: professional self-determination; high school student; innovative profession; professional identification; professional behavioral norm; choice of profession